Medi-Hub, TBI: An ecosystem for business development in medicinal and aromatic plants - Patel, Snehalkumar; Singh, Ritu; Patel, Deepa; Basak, B B; Saran, P L; Kumar, Satyanshu; Das, Manish; Reddy, R Nagaraja (Indian Horticulture, 2023)
Medi-Hub Technology Business Incubator (Medi-Hub, TBI) is an agri-business incubator looking at all aspects of business development in the field of medicinal and aromatic plants. First of its kind to cater start-ups needs in medicinal and aromatic plants, the incubator was commissioned at ICAR-DMAPR, Anand. Medi-Hub TBI is encouraging the budding entrepreneurs to promote the growth of medicinal and aromatic plants sector by providing incubation support to convert idea and business enterprise. The services provided by Medi-Hub, TBI include technology consultation, business consultation, mentoring and networking, infra facilities, access to funding and knowledge sharing to foster business development. It has rendered incubation support to 30 novel business ideas in the herbal sector. Business aspirants/entrepreneurs having novel business ideas can join Medi-Hub, TBI to accelerate business development.